Obsession with Death in the Works of August Antoni Jakubowski and Heinrich von Kleist - Modzelewska, Ewa (Wzniosłość i makabra w literackich obrazach śmierci, 2014)
The aim of this paper is to show the work of two romantic authors, namely Heinrich von Kleist andAugust Antoni Jakubowski. They were not only fascinated by death, but they also died at a young age. Byanalyzing their biographies, poetry and letters I will present utterly different perceptions of death. Kleist,for instance, longed for it like the sick long for a cure. He perceived death as the beginning of a bigadventure, in which he was to be accompanied by Henrietta. They found common ground thanks toa paradoxical decision of dying, not living, together. In addition, I will also discuss the less known workof Jakubowski, the illegitimate son of Antoni Malczewski. He committed suicide at the age of 21, whilebeing on exile in America, right after the November Uprising. Furthermore, I will touch upon his autobiographicalpoems, in which one can notice his maturation towards death as liberation from a foreignworld, without hope of coming back to his homeland. This poetry is a testimony of growing depressionand misery, while the motif of death becomes the author’s obsession.